Comparison of blood serum protein analysis by MALDI-MS from either conventional frozen samples or storage disc-deposited samples: A study with human serum from pregnant donors and from patients with intrauterine growth restriction. Issue 4 (August 2019) - Wölter, Manja; Russ, Manuela; Okai, Charles A; Rath, Werner; Pecks, Ulrich; Glocker, Michael O
Mass spectrometric profiling of intact serum proteins, i.e. determination of relative protein abundance differences, was performed using two different serum sample preparation methods: one with frozen and thawed serum, the other with at room temperature deposited and dried serum. Since in a typical clinical setting freezing of serum is difficult to achieve, sampling at room temperature is preferred and can be met when using the Noviplex™ card system. Once deposited and dried, serum proteins can be stored and shipped at room temperature. After resolubilization of serum proteins from "dried serum spots", mass spectra of high quality have been recorded comparable to those that were obtained using fresh-frozen and subsequently thawed serum samples. Differentiation between patients with intrauterine growth restriction and control individuals was achievable, independent from the sample work-up procedure. Having at hand a reliable and robust method for serum storage and shipment which works at room temperature bridges the gap between the clinics and the protein analysis laboratory. Our novel serum handling protocol reduces costs for both, storage and shipping, and ultimately enables clinical risk assessment based on mass spectrometric determination of intact protein abundance profiles.